2010
DOI: 10.1183/09031936.00154209
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a delay in intensive care unit admission for community-acquired pneumonia

Abstract: The primary objective of the present study was to evaluate the effect on hospital mortality of a delay in intensive care unit (ICU) admission for severe community-acquired pneumonia (CAP). The secondary objectives were to assess if such delays were associated with treatment variations by the emergency department (ED) and deterioration in the general wards, and to evaluate the prognostic ability of the Infectious Disease Society of America (IDSA)/ American Thoracic Society (ATS) minor criteria.We retrospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
83
2
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 25 publications
6
83
2
4
Order By: Relevance
“…Not surprisingly, patients admitted to the ICU after initial triage to the ward had substantially poorer outcomes, including 30-day mortality, compared with those sent straight to the ICU from the emergency department. Almost identical findings were demonstrated in a study from Singapore (19). Mortality was again substantially higher in patients admitted to the floor (72.7%) than those admitted to the ICU initially (33.3%) with more than three IDSA/ATS minor criteria (12).…”
Section: Site Of Caresupporting
confidence: 73%
See 1 more Smart Citation
“…Not surprisingly, patients admitted to the ICU after initial triage to the ward had substantially poorer outcomes, including 30-day mortality, compared with those sent straight to the ICU from the emergency department. Almost identical findings were demonstrated in a study from Singapore (19). Mortality was again substantially higher in patients admitted to the floor (72.7%) than those admitted to the ICU initially (33.3%) with more than three IDSA/ATS minor criteria (12).…”
Section: Site Of Caresupporting
confidence: 73%
“…In keeping with this hypothesis, French and colleagues (25) studied the efficacy of the 7-valent conjugate pneumococcal vaccine in a randomized, double-blind, placebo-controlled study of 496 adolescents and adults in Malawi, 89% of whom were infected with HIV. The primary endpoint of the study, infection due to serotype 6A covered by the 7-valent vaccine, showed a substantial reduction in events in the vaccine group (5 vs. 19). The overall value of the vaccine was limited by the finding that 64% of pneumococcal infections were by nonvaccine serotypes; it is hoped that coverage will improve as higher-valent conjugate vaccines become available.…”
Section: Vaccine Preventionmentioning
confidence: 99%
“…Accordingly, a multicentre database in the USA previously found that only a small proportion of patients experiencing cardiac arrest while hospitalised with pneumonia showed features of severe CAP, such as shock (33%) or mechanical ventilation (36%), and 38% of arrests occurred in a normal ward with only 52% being under cardiorespiratory monitoring [4]. Clinical deterioration, septic organ dysfunction or death predominantly occur within a well-defined time frame of 24-72 h after hospitalisation [2,[4][5][6]. For this vulnerable early period, interventions like intensive monitoring and management in the intensive care unit (ICU) [6][7][8], optimised sepsis management (''sepsis bundles'') [9] and early adequate antibiotic therapy [10,11] potentially translate into substantial prognosis improvement.…”
mentioning
confidence: 99%
“…The authors found that the patient group awaiting ICU admission for over 6 hours were hospitalized for longer periods in the ICU (10.7 vs 8.4 days) and hospital mortality was higher (17.4% vs 12.9%). The problem is aggravated by the fact that individuals with increased length of stay in the ICU are more exposed to infections, have less favorable prognosis, and incur higher hospital costs, which together have an evident negative impact on the observed outcome 14,15 . It is worth highlighting that a tertiary university hospital serves as reference for performance of highly complex procedures, so there is a real need for adjustment of the number of ICU beds.…”
Section: Discussionmentioning
confidence: 99%